2017
DOI: 10.1017/s1368980017003457
|View full text |Cite
|
Sign up to set email alerts
|

Thinness in young schoolchildren in Serbia: another case of the double burden of malnutrition?

Abstract: A rather high prevalence of thinness highlights this malnutrition disorder as an emerging health issue that should trigger public health policies to tackle thinness, especially in girls of young age and children living in economically disadvantaged areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…Furthermore, the dependencies are similar to those of the population thus making this a nationally representative sample of Polish children [16]. This result is also supported by international research [26][27][28]. Age differences mainly refer to the older group where the prevalence of thinness was significantly higher in girls (14.5%) than in boys (11.1%), also confirming the tendency of girls' thinness to increase with age [29,30].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, the dependencies are similar to those of the population thus making this a nationally representative sample of Polish children [16]. This result is also supported by international research [26][27][28]. Age differences mainly refer to the older group where the prevalence of thinness was significantly higher in girls (14.5%) than in boys (11.1%), also confirming the tendency of girls' thinness to increase with age [29,30].…”
Section: Discussionsupporting
confidence: 80%
“…Age differences mainly refer to the older group where the prevalence of thinness was significantly higher in girls (14.5%) than in boys (11.1%), also confirming the tendency of girls' thinness to increase with age [29,30]. Generally, the prevalence of thinness in Polish children is higher than in other European countries or Australia and USA, where thinness among children and adolescents is about 4%-9% [26,28,31,32]. The increasing percentage of children, especially older girls, with body weight deficiencies observed between 1977 and 2004 [8] in the Polish population is also alarming.…”
Section: Discussionsupporting
confidence: 52%
“…We did not collect information on foods' portion sizes to identify chilren's prevalence meeting specific nutrition recommendations. Our study identified a negative trend of underweight, overweight, and obesity pandemic among Serbian children compared to our previous reports (3,24). We found some bright spots in dietary habits, such as the high prevalence of Serbian children that regularly consume breakfast and some areas that require improvements, including low fruit and vegetable and high nutrition-poor food consumption.…”
Section: Discussionsupporting
confidence: 57%
“…Overweight and obesity in children are among the most severe public health problems that have increased dramatically during the last decades at the global and European levels ( 1 ). According to estimates from the World Health Organization (WHO), around 1 in 3 children in Europe aged 6–9 years old were overweight or obese ( 2 ), while reports from eight European countries suggest varied prevalence for underweight, from 5.7% in Italian boys to 16.6% for girls in Hungary ( 3 , 4 ). Being overweight during childhood is associated with obesity and adverse health consequences throughout the life-span ( 5 ), reducing the average age at which non-communicable diseases and disabilities or the likelihood of mortality become apparent ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research from the latest round of the WHO European Childhood Obesity Surveillance Initiative (COSI) carried out in 2015–2017 indicates that 29% of boys and 27% of girls aged seven to nine years had overweight and there was a prevalence of obesity of 12% in boys and 9% in girls [ 6 ]. At the same time, in certain parts of the WHO European Region, there is a double burden of malnutrition, characterized by the coexistence of undernutrition (being underweight for one’s age, too short for one’s age (stunted), too thin for one’s height (wasted), or deficient in vitamins and minerals (micronutrient malnutrition)), along with overweight, obesity, or noncommunicable diseases, within individuals, households, and populations, and across the life course [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%